Hybrid nanodiamond quantum sensors enabled by volume phase transitions of hydrogels - Ting Zhang (Nature Portfolio, 2018)
Nitrogen-vacancy (NV) centers in diamonds are used for quantum sensing but NV centers are not sensitive to parameters such as temperature, pressure and biomolecules. Here the authors propose a scheme based on a magnetic nanoparticle docked responsive hydrogel which acts as a transducer between the particles and the diamond.